Superconductivity under pressure and low temperature specific heat of ThPr alloys - Huber, J. G.; Bulman, J. B.; Sereni, J. G. R.; Sereni, Julián (Pergamon Press, 1982)
Fil: Huber, J. G. University of Kentucky; Estados Unidos